Pengembangan Kedai Kopinggir dengan Mengoptimalkan Promosi Melalui Media Digital - Ita Purnama; Syrilus Alexander Alvaro Roja; Alief Sofyan Lanang (Indo Publishing, 2025)
Digital transformation has significantly changed the culinary business landscape, especially for small businesses such as coffee shops. This study aims to develop a digital promotion strategy for Kedai Kopinggir, located in Bima City. The research uses a descriptive qualitative approach with data collection techniques including observation, interviews, documentation, and literature review. The findings reveal that although Kedai Kopinggir has utilized social media platforms such as Instagram and TikTok, its promotional content is still not optimal in terms of introducing its products in detail and reaching a broader audience. Based on the SWOT analysis, recommended strategies include creating a regular content calendar, using language that suits the target market, maximizing social media features, and collaborating with local influencers. With a focused strategy, digitalization is expected to enhance brand awareness and increase the competitiveness of Kedai Kopinggir in the local coffee shop market.